2011
DOI: 10.15517/lank.v11i1.18315
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Madagascar’s granite outcrop orchids: the influence of fire and moisture

Abstract: Quelle est la réponse aux perturbations, et la limitation de l’humidité, par des taxons similaires basés sur l’hétérogénéité des micro-site de l’habitat? Pour cette étude nous avons examiné comment la disponibilité de feu et de l’humidité influence la répartition des orchidées endémiques malgaches spécifique des affleurements de granit (inselbergs). Trois ans après le passage du feu, nous avons compare les modes de distribution et l’abondance d’orchidées dans un habitat d’une mosaïque comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…One of the principal threats in the CHM habitats is fire (Hermans et al 2007 ; Whitman et al 2011 ) and a number of lithophytic orchids may be more prone to threats of extinction from the studied habitats than terrestrial orchids. This group of vulnerable taxa from the CHM should be prioritised and targeted for ex situ collections with IVC as a potential tool to complement conventional seed collecting.…”
Section: Discussionmentioning
confidence: 99%
“…One of the principal threats in the CHM habitats is fire (Hermans et al 2007 ; Whitman et al 2011 ) and a number of lithophytic orchids may be more prone to threats of extinction from the studied habitats than terrestrial orchids. This group of vulnerable taxa from the CHM should be prioritised and targeted for ex situ collections with IVC as a potential tool to complement conventional seed collecting.…”
Section: Discussionmentioning
confidence: 99%
“…Whitman et al . [ 98 ] reported that lithophytic Angraecinae are tolerant to limited moisture availability, and chronic bushfire did not kill the population of Angraecum sororium and Jumellea rigida but only reduced their expansion. But diversification slowdown could be also the result of ecological limitation, competition, access to pollinators, species carrying capacity [ 99 , 100 ], or maintenance of niche similarity [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spatial distribution patterns of P. stachyodes (clustered occurrence at short spatial scales shifting to random occurrence with distance, combined with clumped abundance) are not surprising, given models of orchid seed dispersal patterns (Kindlmann et al 2014), and field observations reported in both temperate and tropical habitats (e.g., Jacquemyn et al 2007, Whitman et al 2011. These spatial patterns are also common with tropical tree species (Condit et al 2000) and may reflect either dispersal limitation or highly specific niche requirements (Brown et al 1995).…”
Section: Discussionmentioning
confidence: 84%
“…Habitat characteristics that promote larger sized P. stachyodes, and thus greater reproductive effort and eventual seed output, are not necessarily the same conditions needed for seedling establishment or the maintenance of subpopulations. Disjunction between habitat needs at different life stages is feasible, given the overall ecological complexity attributed to this taxonomic group (Givnish 1982, Jacquemyn et al 2007, Whitman et al 2011, Bunch et al 2013. For instance, specificity of tree host substrate was not linked to adult orchid fitness or probability of flowering, but may be attributed to conditions necessary for early life stages (Gowland et al 2011).…”
Section: Linking Habitat Characteristics With Possible Life History Smentioning
confidence: 99%